Participative Management of School Administrators Under the Secondary Educational Service Area Office Bangkok 2 - Maha, Chanayus; Thongprong, Amnuay (Legal State Journal, 2024)
This research article aims to study the participative management of school administrators under the Secondary Educational Service Area Office Bangkok 2; and compares the participative management of school administrators under the Secondary Educational Service Area Office Bangkok 2 as classified by educational qualification,academic standing and work experience. The quantitative research approach was employed. The samples used in the research were 357 teachers in schools under the participative management of school administrators under the Secondary Educational Service Area Office Bangkok 2 in the academic year 2023. The instrument used to collect the data was a 5-point rating scale questionnaire with the discrimination values between 0.80-1.00, and the reliability value of 0.97. The statistics used in data analysis were frequency, percentage, mean, standard deviation, t-test, One-Way ANOVA and Scheffé’s multiple comparison method. Findings are as follows: (1) The participative management of school administrators under the Secondary Educational Service Area Office Bangkok 2 both overall and each aspect were high. (2) Teachers who taught at schools of different educational qualification displayed corresponding differences in their opinions of the participative management of school administrators overall and for all aspects at the statistically significant level of .05. (3) Teachers who taught at schools of different academic standing displayed corresponding differences in their opinions of the participative management of school administrators overall at the statistically significant level of .05. (4) Teachers who differed in work experience did not exhibited concomitant differences in their opinions of the participative management of school administrators overall.